The lysine deacetylase inhibitor givinostat inhibits β-cell IL-1β induced IL-1β transcription and processing - Dahllöf, Mattias S. (Landes Bioscience, 2012)
Aims: Pro-inflammatory cytokines and chemokines, in particular IL-1β, IFNγ, and CXCL10, contribute to β-cell failure and loss in DM via IL-1R, IFNγR, and TLR4 signaling. IL-1 signaling deficiency reduces diabetes incidence, islet IL-1β secretion, and hyperglycemia in animal models of diabetes. Further, IL-1R antagonism improves normoglycemia and β-cell function in type 2 diabetic patients. Inhibition of lysine deacetylases (KDACi) counteracts β-cell toxicity induced by the combination of IL-1 and IFNγ and reduces diabetes incidence in non-obese diabetic (NOD) mice. We hypothesized that KDACi breaks an autoinflammatory circuit by differentially preventing β-cell expression of the β-cell toxic inflammatory molecules IL-1β and CXCL10 induced by single cytokines. Results: CXCL10 did not induce transcription of IL-1β mRNA. IL-1β induced β-cell IL-1β mRNA and both IL-1β and IFNγ individually induced Cxcl10 mRNA transcription. Givinostat inhibited IL-1β-induced IL-1β mRNA expression in INS-1 and rat islets and IL-1β processing in INS-1 cells. Givinostat also reduced IFNγ induced Cxcl10 transcription in INS-1 cells but not in rat islets, while IL-1β induced Cxcl10 transcription was unaffected in both. Materials and Methods: INS-1 cells and rat islets of Langerhans were exposed to IL-1β, IFNγ or CXCL10 in the presence or absence of KDACi (givinostat). Cytokine and chemokine mRNA expressions were quantified by real-time qPCR, and IL-1β processing by western blotting of cell lysates. Conclusion/Interpretation: Inhibition of β-cell IL-1β expression and processing and Cxcl10 transcription contributes to the β-cell protective actions of KDACi. In vitro β-cell destructive effects of CXCL10 are not mediated via IL-1β transcription. The differential proinflammatory actions of KDACs may be attractive novel drug targets in DM.